If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(ab + bc + ca) = 202 Reorder the terms: 2(ab + ac + bc) = 202 (ab * 2 + ac * 2 + bc * 2) = 202 (2ab + 2ac + 2bc) = 202 Solving 2ab + 2ac + 2bc = 202 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2bc' to each side of the equation. 2ab + 2ac + 2bc + -2bc = 202 + -2bc Combine like terms: 2bc + -2bc = 0 2ab + 2ac + 0 = 202 + -2bc 2ab + 2ac = 202 + -2bc Reorder the terms: -202 + 2ab + 2ac + 2bc = 202 + -2bc + -202 + 2bc Reorder the terms: -202 + 2ab + 2ac + 2bc = 202 + -202 + -2bc + 2bc Combine like terms: 202 + -202 = 0 -202 + 2ab + 2ac + 2bc = 0 + -2bc + 2bc -202 + 2ab + 2ac + 2bc = -2bc + 2bc Combine like terms: -2bc + 2bc = 0 -202 + 2ab + 2ac + 2bc = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-101 + ab + ac + bc) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-101 + ab + ac + bc)' equal to zero and attempt to solve: Simplifying -101 + ab + ac + bc = 0 Solving -101 + ab + ac + bc = 0 Move all terms containing a to the left, all other terms to the right. Add '101' to each side of the equation. -101 + ab + ac + 101 + bc = 0 + 101 Reorder the terms: -101 + 101 + ab + ac + bc = 0 + 101 Combine like terms: -101 + 101 = 0 0 + ab + ac + bc = 0 + 101 ab + ac + bc = 0 + 101 Combine like terms: 0 + 101 = 101 ab + ac + bc = 101 Add '-1bc' to each side of the equation. ab + ac + bc + -1bc = 101 + -1bc Combine like terms: bc + -1bc = 0 ab + ac + 0 = 101 + -1bc ab + ac = 101 + -1bc The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3.5/8=x/38 | | 655465465+65465654= | | 4x+2x+4x+4y-y=2x | | (100-2x)=180-x^2 | | 4/10=x/38 | | 3/a=a-2 | | x+(2x+3)=19.8 | | 6(m+n)=6m+6n | | 5(x-10)=2x(x-10) | | -3=x^2-5x | | x(2x+3)=19.8 | | 16/x=12/6 | | 3y+y=24+y | | X/75=9/15 | | 2*3x=50 | | 8x-3x=2x+3x | | 24-X+4X=48 | | 46x+33=33+46x | | 7/8=x/20 | | n/3-6=-4 | | 60=5(z+7) | | -4x-4(-13+4x)=12 | | 6=3b*9 | | 100+250= | | 2x-3xy=0 | | 16=25-3b | | 14y=-36 | | -(m+1)(m+3)= | | 7p-18=10 | | 37.68/4 | | 9x-11=2x+8 | | 3x^4-2x^3-12x^2+8x=0 |